Innovation Capacity and the City The Enabling Role of Design - Concilio, Grazia; Tosoni, Ilaria; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book is licensed under a Creative Commons Attribution 4.0 International License. .
Introduction -- A Triplet under focus: innovation, design, city -- Cities as enablers of innovation -- Innovation and design -- Design enabled innovation in urban environments.
Keywords: Sociology, Urban; Urban economics; Urban Sociology; Urban Economics